NEUROSAINS PADA THINK TALK WRITE (TTW) DALAM MENULIS TEKS PUISI - Aini Ulwi Sifa; Dida Firmansyah; Diena San Fauziya (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The brain is a hard instrument that is attached to a person. Therefore, the source of human intelligence comes from the working system of the brain. Brain performance is suitable for use in brain-friendly learning activities with a high artistic level. For this reason, the purpose of this study was to determine student responses to the study of poetry text learning using a neuroscience approach through the Think Talk Write method in the digitalization era. This research uses descriptive type in the form of case study research. In analyzing sources or data, applying observation techniques that are guided by student responses during learning activities, as well as student results by the rules, namely choosing the right diction, using figurative language, distinctive image power, containing meaning, alignment of title and content. The results of the study prove that students become more active and can understand theoretically and empirically in learning to write texts first supported by LKPD which can stimulate students in arguing.